Small calcium isotope fractionation at slow precipitation rates in methane seep authigenic carbonates. (1st April 2021) - Blättler, Clara L.; Hong, Wei-Li; Kirsimäe, Kalle; Higgins, John A.; Lepland, Aivo
Abstract: Natural calcium carbonate minerals express a range of calcium isotope fractionations, with the precipitated mineral typically enriched in the lighter isotopes of calcium relative to source fluids. Experimental and theoretical evidence shows a strong dependence on precipitation rate, although this relationship has not been well quantified over the range of precipitation rates observed in natural settings. Endmember cases show that average marine carbonate precipitation expresses a large fractionation ( δ 44 / 40 Ca values lower than seawater by approximately 1‰), while diagenetic carbonate phases assumed to have precipitated or recrystallized at very slow rates show negligible fractionation. The limited examples of quantified precipitation rates in natural settings with measurable, non-zero fractionation represents a barrier for applying mechanistic models of calcium isotope fractionation to geological applications. This study examines a methane seep system in the northern Barents Sea south of Svalbard where authigenic carbonate minerals are precipitating, driven by anaerobic oxidation of methane, and where the apparent calcium isotope fractionation factor and precipitation rate can be constrained by measuring properties of the pore fluids. Pore fluid profiles are analyzed in two shallow cores, and authigenic carbonate nodules are analyzed in one of these cores. The pore fluid profiles point to a transitional, non-steady state which approximates a closed system, where the elevation of pore fluid calcium isotope ratios through carbonate precipitation can be modeled as a Rayleigh distillation system. The apparent fractionation factors for 44 Ca/ 40 Ca ratios at these sites are α = 0.99985 and 0.9996, although the carbonate nodules suggest a different calcium isotope fractionation factor may have been expressed under past conditions. Precipitation rates at the two sites are estimated to be 1.4 and 3.5 μmol/m 2 /h, intermediate between those of typical laboratory experiments and the much slower rates of marine diagenesis. Trace element analyses of the nodules (Mg/Ca and Sr/Ca ratios) suggest that both precipitation rate and mineralogy affect nodule composition. These results provide new constraints for the relationship between precipitation rate and calcium isotope fractionation and can inform modeling efforts leading towards mechanistic understanding of calcium isotope fractionation and trace element distributions in carbonate minerals.